PERLINDUNGAN HAK PELAKU USAHA DAN HAK KONSUMEN DALAM PELAKSANAAN REPLANNING KAWASAN PERUMAHAN KOMERSIAL - Wibisana, Nicholas Ardy; Hermawan, Ariyanto; Nalle, Victor Imanuel Wiliamson; Anakotta, Marthsian Yeksi (Universitas Muhammadiyah Ponorogo, 2024)
This article discusses the issue of conflict between the rights of business actors to do replanning housing areas regulated in Perwali Surabaya Nomor 52 Tahun 2017 with consumer rights as guaranteed in Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen in relation to the principles of legal certainty, principles of justices and the presence of the state in fulfilling in the rights of its citizens. The research used is normative juridical research using a case approach, statute approach and conceptual approach. The research results show that there are regulatory conflicts in relation to changes that can be made by business actors, especially with regard to PSU, which is also one of the parts that buyers as consumers have rights to. Apart from that, the research results also show that there are various weaknesses in the form of indecisiveness and inconsistency in the use of terminology in both the Housing and Residential Areas Law and the Consumer Protection Law. This proves the importance of improving and harmonizing laws and regulations in order to implement the principle of integration and guarantee the rights of the parties fairly.